2010
DOI: 10.1002/esp.2088
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the effects of floodplain vegetation on river planform style

Abstract: The effects of floodplain vegetation on river planform have been investigated for a medium-sized river using a 2D morphodynamic model with submodels for flow resistance and plant colonization. The flow resistance was divided into a resistance exerted by the soil and a resistance exerted by the plants. In this way it was possible to reproduce both the decrease in bed shear stress, reducing the sediment transport capacity of the flow within the plants, and the increase in hydraulic resistance, reducing the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 42 publications
3
119
0
Order By: Relevance
“…Furthermore, the opposite process of bank erosion, which is bar-floodplain conversion by, for example, vegetation encroachment, is not considered in Delft3D. The necessity of this bar-floodplain conversion for channel migration was demonstrated by Schuurman et al (2016), and the large effect of riparian vegetation on braiding river morphology has previously been demonstrated by, for example, Murray and Paola (2003) and Crosato and Saleh (2010). This missing mechanism must be included to fully understand the contribution of floodplain-channel interaction on the morphodynamics in braiding rivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the opposite process of bank erosion, which is bar-floodplain conversion by, for example, vegetation encroachment, is not considered in Delft3D. The necessity of this bar-floodplain conversion for channel migration was demonstrated by Schuurman et al (2016), and the large effect of riparian vegetation on braiding river morphology has previously been demonstrated by, for example, Murray and Paola (2003) and Crosato and Saleh (2010). This missing mechanism must be included to fully understand the contribution of floodplain-channel interaction on the morphodynamics in braiding rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Many river modeling studies have applied constant discharge, assuming a morphologically dominant or representative discharge exists that gives similar yearly morphodynamics to the "real" hydrograph (e.g., Nicholas, 2010;Schuurman et al, 2013). However, other studies have shown that discharge variation has a large effect on river morphology (e.g., Kiss and Sipos, 2007;Crosato and Saleh, 2010) due, among other things, to vegetation colonization on exposed bar sections (Gordon and Meentemeyer, 2006;Tealdi et al, 2011). Also, Egozi and Ashmore (2009) demonstrated that braiding intensity increased with increasing discharge, although this was temporary and braiding intensity decreased after the channel adapted to the new discharge.…”
Section: Disturbances In Braiding Riversmentioning
confidence: 99%
“…1) is successfully used in other studies with real vegetation: such as the simulation of the flow field over a river floodplain with grass, reed and softwood [48,49], and marsh vegetation [50]. Following the approach of Baptist et al [1], the representative Chézy value at every location with vegetation is described by (Eq.…”
Section: Environ Fluid Mechmentioning
confidence: 99%
“…Klaassen and Van der Zwaard, 1974). These include theoretical principles of the mathematical modelling of the phenomenon (Baptist et al, 2007;Horritt, 2006;Klopstra et al, 1997;Wu et al, 2001;Yang and Choi, 2010), numerical modelling with models of varying complexity (Crosato and Saleh, 2011;Perona et al, 2009;Velasco et al, 2008), flume experiments to verify models of vegetation roughness and in situ floodplain roughness estimations (Meijer and van Velzen, 1999;Murphy et al, 2007;Straatsma, 2009;Tal and Paola, 2010). Some studies focused on the accumulation of both thick and fine debris (Mazur et al, 2016) carried along with the flood wave.…”
Section: Introductionmentioning
confidence: 99%